Comparative Study on Fatty Acid Profiles of Anchovy from Black Sea and Mediterranean Sea (Engraulis encrasicholus L., 1758) - OKSUZ, ABDULLAH; OZYILMAZ, AYSE; TURAN, CEMAL (Asian Journal of Chemistry, 2010)
Fatty acid profile of anchovies (Engraulis encrasicholus) from Black Sea and Mediterranean Sea were determined by using GC-MS. A total of 25 fatty acids were identified. The level of saturated fatty acids (SFA), monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) were found as almost 38, 14.3 and 47.7 % in Mediterranean anchovy (MA), respectively. These levels were followed by 35.40 % (SFA), 29.5 % (MUFA) and 31.27 % (PUFA) in Black Sea anchovy (BSA). Geographical location has no effect on total saturated fatty acids of anchovy, whereas MUFA and PUFA changed significantly. BSA contained greater amount of MUFA and low level of PUFA. Conversely, MA had high level of PUFA and low level of MUFA compare to BSA. The ratio of DHA to EPA was calculated as 5.91 in MA and 1.64 in BSA. Palmitic acid, oleic acid and DHA (22:6 n3) were themost prominent fatty acid in both MA and BSA. DHA level may be considered as a key fatty acid to differentiate MA from the BSA.